2021
DOI: 10.3390/foods10122974
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Biochemical Composition Characteristics of Arthrospira platensis Induced by Simultaneous Nitrogen Deficiency and Seawater-Supplemented Medium in an Outdoor Raceway Pond in Winter

Abstract: Arthrospira platensis, a well-known cyanobacterium, is widely applied not only in human and animal nutrition but also in cosmetics for its high amounts of active products. The biochemical composition plays a key role in the application performance of the Arthrospira biomass. The present study aimed to evaluate the growth and biochemical composition characteristics of A. platensis, cultured with a nitrogen-free and seawater-supplemented medium in an outdoor raceway pond in winter. The results showed that the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…In this study, we observed that the inclusion of dietary A. platensis at a high-level increased glucose levels in birds fed the enzyme mixture relative to the reference diet. This finding is most probably associated with the carbohydrate-rich composition of A. platensis ( 44 , 45 ). Interestingly, while creatinine levels were enhanced by Spirulina extruded or combined with enzymes, a significant reduction in urea was observed in birds fed A. platensis , individual or extruded relative to the other treatments.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, we observed that the inclusion of dietary A. platensis at a high-level increased glucose levels in birds fed the enzyme mixture relative to the reference diet. This finding is most probably associated with the carbohydrate-rich composition of A. platensis ( 44 , 45 ). Interestingly, while creatinine levels were enhanced by Spirulina extruded or combined with enzymes, a significant reduction in urea was observed in birds fed A. platensis , individual or extruded relative to the other treatments.…”
Section: Discussionmentioning
confidence: 88%
“…Arthrospira sp. contains an abundance of protein (60–70% of dry weight, DW), carbohydrates (15–25% of DW), lipids/PUFAs (3–9% of DW), and other nutrients, making it suitable as a functional food ( Wu et al., 2021 ; AlFadhly et al., 2022 ). In addition, Arthrospira spp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Arthrospira spp. contain abundant phycocyanin, a blue photosynthetic pigment utilized in the food, cosmetic, and pharmaceutical industries ( Wu et al., 2021 ). These commercial advantages have led to the widespread cultivation of Arthrospira spp.…”
Section: Introductionmentioning
confidence: 99%
“…Spirulina stands out due to its high protein content (up to 76% of dry matter, DM) [ 5 , 6 ], essential amino acids, carbohydrates (up to 22.6% DM) [ 5 ] and unique pigment composition, which includes phycocyanin, carotenoids and chlorophylls [ 7 , 8 , 9 ]. These components not only enhance the growth performance of broilers but also positively impact meat quality [ 5 ].…”
Section: Introductionmentioning
confidence: 99%